(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
This article explains how the liberal army established improvised armorers and melted church bells in the midst of the Reform War to recover lost artillery. The technical aspects of the handcrafted production of cannons and their use and importance in the war are analyzed. The origin of the popular resistance to lowering bells and the anticlericalism of some sectors of society, which played in favor of the liberals, are also interpreted.